Ocular Findings in the 16p11.2 Microdeletion Syndrome: A Case Report and Literature Review - Cybil S. Stingl; Colleen Jackson-Cook; Natario L. Couser (Case Reports in Pediatrics)
The recurrent 16p11.2 microdeletion is characterized by developmental delays and a wide spectrum of congenital anomalies. It has been well reported that individuals with this ∼593-kb interstitial deletion have an increased susceptibility toward the autism spectrum disorder (ASD). Abnormalities of the eye and ocular adnexa are also commonly associated findings seen in individuals with the 16p11.2 microdeletion syndrome, although these ophthalmic manifestations have not been well characterized. We conducted an extensive literature review to highlight the eye features in patients with the 16p11.2 microdeletion syndrome and describe a 5-year-old boy with the syndrome. The boy initially presented with intellectual disability, speech delay, and defiant behavior; diagnoses of attention deficit hyperactivity disorder (ADHD) and oppositional defiant disorder (ODD) were established. He had a Chiari malformation type 1. His ophthalmic features included strabismus, hyperopia, and ptosis, and a posterior embryotoxon was present bilaterally. From a systematic review of prior reported cases, the most common eye and ocular adnexa findings observed were downslanting palpebral fissures, deep-set eyes, ptosis, and hypertelorism.